Where is the missing chicken bone? A case of foreign body cystic bronchiectasis - Zainal, Nur Farhanah; Haroon, Raihanah; Ahmad, Nur Fathihah (IIUM Journal of Orofacial and Health Sciences, 2023)
Aspiration of foreign body among adult usually occur in geriatric populations and those with impaired airway reflexes from a neurologic abnormality, altered mental status resulting from sedative or alcohol use, or trauma with decreased levels of consciousness. Symptoms are usually acute requiring prompt intervention. Longstanding neglected foreign body aspiration can cause irreversible damage to the lung parenchyma and respiratory tract with residual respiratory sequalae. Here we present a rare case of a healthy lady who experience chronic productive cough and recurrent chest infections due to neglected foreign body aspiration leading to irreversible cystic bronchiectasis of the lung.